Synthesis And characterization Of New Type Of Biodegradable Polyurethane Containing Azo Derivatives Of Benzocaine - Mohammed A. Mutar; Sabrean F. Jawad (Al-Qadisiyah Journal of Pure Science, 2018)
In this work a series of new types of biodegradable and pH-sensitive polyurethane containing azo derivatives of Benzocaine were synthesized by the condensation polymerization of 1,6-hexamethylene diisocyanate at the temperature 80 Î¿C with the azo monomers . The monomers synthesized from the reaction of (1-naphthole M1, 4-bromophenol M2, phenol M3 , and p-hydroxy acetophenone M4 ):With acetone in presence of HCl as catalyst by refluxing for 6 hrs at 60Î¿C.The azo monomers were synthesized from the reaction of monomers : (M1 ,M2 ,M3 ,M4 ) with Benzocaine in presence of HCl , NaNO2 and NaOH 10% by stirring for one hour in ice bath at (0-5 Î¿C) .polyurethane azo were synthesized from the reaction between the azo monomers with 1,6- hexamethylene diisocyanate in oil bath by refluxing for 8 hours at 80 Î¿C in dry nitrogene.U.V-Visible , FT-IR , H1NMR techniques were used to confirm the chemical structure of the synthesized Polyurethane azo.A calibration curve between absorbance and concentration was constructed to stock solution of pure drug. the concentration of Benzocaine release was calculated by extrapolation of the result on the calibration curve every 24 hrs. the detection limit for Benzocaine was minimum used 0.001 gm/mol wavelength at 293 nm.Benzocaine was loaded into the polymeric matrix during in situ polymerization . the drug release from the Benzocaine loaded was studied in two medias ( pH=7.8, pH=4 ) at body temperature(37Î¿C). also the total amount of released Benzocaine was measured at room temperature and pH=4,pH=7.8 .